German Influences on American Economic Thought and American Influences on German Economic Thought Deutsche Einflüsse auf amerikanisches wirtschaftswissenschaftliches Denken und amerikanische Einflüsse auf deutsches Wirtschaftsdenken. Studien zur Entwicklung der ökonomischen Theorie XXXII - Hagemann, Harald (Schriften des Vereins für Socialpolitik, 2017)
The focus of the nine contributions is on the mutual influences between German and American economic thought. Whereas in the period between 1871 and 1914 the Humboldtian research university was a main attractor for younger American scientists who went to Germany for (post-) graduate studies, WW I and particularly the Nazi period contributed to a decisive shift in the direction of the transfer of knowledge in economics. Émigré economists from Germany and Austria made major contributions to the »Americanization« of economics after WW II.